2017
DOI: 10.1371/journal.pone.0182913
|View full text |Cite
|
Sign up to set email alerts
|

Collective movements of pedestrians: How we can learn from simple experiments with non-human (ant) crowds

Abstract: IntroductionUnderstanding collective behavior of moving organisms and how interactions between individuals govern their collective motion has triggered a growing number of studies. Similarities have been observed between the scale-free behavioral aspects of various systems (i.e. groups of fish, ants, and mammals). Investigation of such connections between the collective motion of non-human organisms and that of humans however, has been relatively scarce. The problem demands for particular attention in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Based on the investigation of the literature related to the notion of geometric designs, particularly the impact of conflicting geometries on crowd dynamic, a number of studies ( 11 , 31 , 32 ) explored the effect of corridor configurations in merging passage using non-human subjects. These experiments have been considered as a proximate model of the scale-free behavior of humans.…”
mentioning
confidence: 99%
“…Based on the investigation of the literature related to the notion of geometric designs, particularly the impact of conflicting geometries on crowd dynamic, a number of studies ( 11 , 31 , 32 ) explored the effect of corridor configurations in merging passage using non-human subjects. These experiments have been considered as a proximate model of the scale-free behavior of humans.…”
mentioning
confidence: 99%
“…Different geometrical and architectural configurations with different level of complexities, e.g., exits and entrances [ 13 17 ], straight corridors [ 18 20 ], crossing [ 21 – 25 ], merging [ 26 30 ], and turning [ 31 34 ] configurations, have been explored in such previous studies using controlled experiments conducted with human subjects. Not only humans, but non-human biological entities, e.g., ants, have also been used to explore the evacuation performance of different geometrical settings under panic conditions [ 35 37 ]. For the design purposes that ensure the safety of crowds and efficiency of crowd flows at general bottleneck scenarios, e.g., exit doors and corridors, several studies have indicated that there is a direct relationship between pedestrian flow and bottleneck width, i.e., increasing pedestrian flows with increasing the bottleneck width and thereby decrease in evacuation time [ 17 , 38 41 ].…”
Section: Related Workmentioning
confidence: 99%
“…The microscopic interaction rules initiate motility-induced phase separation from disordered states to non-uniform macroscopic patterns displaying order (at least partially) 20,21 . Pedestrian and vehicle flows are also systems of interacting self-driven agents that can exhibit phase transitions and self-organisation [22][23][24][25][26] . Indeed, pedestrians and drivers interact locally with their environment and the neighbourhood and have by the way density-dependent motility parameters.…”
Section: Introductionmentioning
confidence: 99%